Endoscopic Ultrasound-Guided Gastroenterostomy for Afferent Loop Syndrome - Hideyuki Shiomi; Arata Sakai; Ryota Nakano; Shogo Ota; Takashi Kobayashi; Atsuhiro Masuda; Hiroko Iijima (Clinical Endoscopy, 2021)
Afferent loop syndrome (ALS) is a mechanical obstruction of the afferent limbs after gastrectomy with gastrojejunostomy reconstruction. Patients with cancer recurrence require immediate and less invasive treatment because of their poor condition. Percutaneous transhepatic/transluminal drainage (PTD) and endoscopic enteral stenting offer reasonable palliative treatment for malignant ALS but are not fully satisfactory in terms of patient quality of life (QoL) and stent patency. Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) using a lumen-apposing metal stent may address these shortcomings. Clinical data from 11 reports showed that all patients who had undergone EUS-GE had positive technical and clinical outcomes. The adverse event rate was 11.4%, including only mild or moderate abdominal pain, with no severe adverse events. Indirect comparative studies indicated that patients who had undergone EUS-GE had a significantly superior QoL, a higher clinical success rate, and a lower reintervention rate than those who had undergone PTD or endoscopic enteral stenting. Although the evidence is limited, EUS-GE may be considered as a first-line treatment for malignant ALS because it has better clinical outcomes than other less invasive treatments, such as PTD or endoscopic enteral stenting. Further prospective randomized control trials are necessary to establish EUS-GE as a standard treatment for ALS.